Senyapan dan Kilir Lidah pada Tuturan Mahasiswa Uji Kompetensi Kepenyiaran di Universitas PGRI Semarang: Silence and Slip of the Tongue in the Speech of Students in the Broadcasting Competency Test at PGRI University Semarang - Larasati Ekananda Cahyani; Arisul Ulumuddin; Rawinda Fitrotul Mualafina (Universitas Tidar, 2025)
This study aims to analyze silence and slips of the tongue that occur in students' speech during the broadcasting competency test. The focus of the study is on identifying the types, characteristics, and factors that influence silence and slips of the tongue in the practice of broadcasting news. The research method used is descriptive qualitative with a free-speech observation data collection technique, where researchers observe students' speech without being directly involved in the communication process. Data were obtained from videos of news broadcasting practices during the broadcasting competency test. Then, the data were analyzed using the matching method. The results of the study showed that the silence that predominantly appeared was silent pause. The identified slips of the tongue include semantic errors, syllable errors, word errors, anticipation, deletion, and spoonerism. These findings contribute to the evaluation of speaking skills learning towards understanding speech fluency disorders in an academic context and can be used as a basis for developing effective communication learning strategies for students, especially in broadcasting competency tests.